2010
DOI: 10.1111/j.1468-2389.2010.00511.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Passing the Professional in Human Resources Exam on Early Career Success for Undergraduates Entering the Human Resource Field

Abstract: This study investigates the impact of passing the Professional in Human Resources (PHR) certification exam on the early career success of recent college graduates. Data were gathered from alumni of three Midwestern universities who earned an undergraduate degree in business administration (i.e., BBA) with a major in human resources. The survey was designed to measure early career success indicators including finding a job in the HR field, starting salary, and number of promotions. Results reveal that the proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 18 publications
3
22
0
1
Order By: Relevance
“…First, respondents who held an HR certification themselves use certification to a greater extent when choosing which candidate to hire. This reinforces the findings of Lester et al (2010) that HR majors who have passed the PHR certification exam are more likely than their counterparts who did not take or did not pass the PHR to obtain a job in the HR field upon graduation. Second, participants who held a non-HR certification indicated that they do not consider HR certification when determining the starting salary of new HR employees.…”
Section: Perceived Benefits Of Hr Certificationsupporting
confidence: 85%
See 1 more Smart Citation
“…First, respondents who held an HR certification themselves use certification to a greater extent when choosing which candidate to hire. This reinforces the findings of Lester et al (2010) that HR majors who have passed the PHR certification exam are more likely than their counterparts who did not take or did not pass the PHR to obtain a job in the HR field upon graduation. Second, participants who held a non-HR certification indicated that they do not consider HR certification when determining the starting salary of new HR employees.…”
Section: Perceived Benefits Of Hr Certificationsupporting
confidence: 85%
“…On a more promising note, Lester et al (2010) found that HR majors who passed the PHR exam were two-and-a-half times more likely to get a job in the HR field upon graduation than those who did not take or did not pass the PHR exam. This suggests that those recruiting for HR positions view this credentialing favorably as it relates to demonstrating competency to successfully perform the job.…”
Section: Human Resource Certificationmentioning
confidence: 99%
“…In contrast, none of the job announcements in transportation and warehouse, and only .7% of job announcements in retail trade required or preferred HR certification. Consistent with this, Lester et al (2010) found that perceptions of the value of HR certification varied greatly across a sample of three Midwestern Universities. For example, one university had a required capstone course for HR majors designed to prepare students for the exam, and only students who passed the PHR exam graduated as HR majors.…”
Section: Differences In the Perceived Value Of Hr Certificationsupporting
confidence: 60%
“…Of the 1873 job announcements they reviewed, only 4.2% required or preferred HR certification. More recently, Lester, Mencl, Maranto, Bourne, and Keaveny (2010) found that university undergraduates who passed the Professional in Human Resource (PHR) certification exam were more than twice as likely to obtain an HR job than those who did not take or did not pass the exam. However, they found that passing the PHR exam was not a significant predictor of starting salary or number of promotions received.…”
Section: Differences In the Perceived Value Of Hr Certificationmentioning
confidence: 98%
“…Outsourcing is also less common for activities such as training delivery and employee rewards and incentives than in functions such as payroll administration and recruiting. Proponents of privatization insist that the prevalence of inflexible, rule-bound public HRM systems has necessitated a higher degree of reliance on contractors who can hire new personnel and dismiss poor performers quickly (Lester et al 2010). The public sector can therefore utilize the capacity of the private sector to accomplish the so-called 3E principles of economy, efficiency, and effectiveness for greater flexibility, which is a key theme of many public sector reform programs (Fernandez andSmith 2006, Chun andRainey 2005).…”
Section: Defining Hrm Outsourcingmentioning
confidence: 98%